Trachea repair using an autologous pericardial patch combined with a 3D carbon fiber stent: A case report - Wang, Bin; Zhang, Zhe; Guo, Yuanwei; Yu, Fenglei (Frontiers in Surgery, 2023)
This study is the first to use an autologous pericardial patch combined with 3D carbon-fiber stent for plastic repair of large trachea defect. Radical surgery is optimal therapy for primary malignant tracheal tumors. Tracheoplasty or repair is required to guarantee the trachea integrity and normal ventilation function after tracheal tumor resection. Here we present a case of plastic repair of trachea using autologous pericardial patch and 3D custom-made carbon-fiber stent. A 4 cm trachea defect was successfully repaired after resection of a malignant schwannoma. The postoperative ventilatory function was normal without obvious symptoms of discomfort. Fiberoptic bronchoscopy showed smooth mucosal surface of the endotracheal wall and patency of the airway. CT scans 3 years after surgery showed no recurrence. We can conclude that 3D carbon-fiber stent is feasible to abolish patch floating and prevent tracheal stenosis.